The influence of ozonized ice on chilled Atlantic salmon (Salmo slar) quality and microbial safety - Bajerkevičiūtė, Rosita; Degutytė, Rimgailė; Šipailienė, Aušra; Tichonovas, Martynas (2018)
Diseases caused by food pathogens became one of the most common health problems in the world. Listeria monocytogenes, one of the most dangerous pathogens, is often found in fresh fish. In order to avoid health risks, researchers are constantly looking for new and better ways to process food, ozonizing being one of them. Ozone is a strong antimicrobial agent and has been successfully used against pathogenic microorganisms, as a disinfectant for water and inactivator of contaminant microflora on various foods.